Seasonal and interannual variability of surface heat and freshwater fluxes in the Mediterranean Sea: budgets and exchange through the Strait of Gibraltar - Criado-Aldeanueva, Francisco; Soto-Navarro, Francisco Javier; García-Lafuente, Jesús (Royal Meteorological Society, 2012)
Several NCEP climatological datasets have been combined to analyse the seasonal and interannual variations of the heat and water budgets in the Mediterranean Sea, and compare the long-term means with direct measurements in the Strait of Gibraltar. The seasonal cycle of the net heat is positive (toward the ocean) between March and September with maximum in June and negative the rest of the year with minimum in December. Although subject to inherent uncertainty, we obtain a practically neutral budget of 0.7 Wm−2 in a yearly basis. The net heat budget is positive for the western Mediterranean (∼12 Wm−2) and negative for the eastern Mediterranean (∼− 6.4 Wm−2) mainly due to the high latent heat losses of this basin. The evaporation minus precipitation (E–P) freshwater deficit has a seasonal cycle with a range of variation about 600 mm·y−1, maximum in August–September and minimum in May. The long-term mean of the basin-averaged deficit is 680 ± 70 mm·y−1 but it is almost 70% greater in the eastern Mediterranean due to higher E and lower P in this basin. Combining the climatological values with in situ measurements in Espartel sill, a mean inflow through the Strait of Gibraltar of 0.82 ± 0.05 Sv is obtained and a salinity ratio Sin/Sout = 0.956. A heat advection Qa = 3.2 ± 1.5 Wm−2 through the Strait of Gibraltar has been obtained that, combined with the long-term averaged surface heat flux, implies that the net heat content of the Mediterranean Sea would have increased in the last decades.
Se adjunta la versión postprint aceptada, que incluye las correcciones de de los revisores, debido a que la editorial tiene los derechos de copyright y no permite la difusión en acceso abierto de la versión publicada. Puede accederse a la misma a través del DOI que se incluye en los datos de la publicación.
Keywords: Hidrodinámica; Mediterráneo; Mediterranean Sea; Heat and freshwater fluxes; Seasonal and interannual variability; Strait of Gibraltar